Congenital heart disease is a feature of severe infantile spinal muscular atrophy. Issue 10 (28th July 2008) - Rudnik-Schöneborn, S; Heller, R; Berg, C; Betzler, C; Grimm, T; Eggermann, T; Eggermann, K; Wirth, R; Wirth, B; Zerres, K
Abstract : Objective: Homozygous deletions/mutations of the SMN1 gene cause infantile spinal muscular atrophy (SMA). The presence of at least one SMN2 gene copy is required for normal embryogenesis. Lack of SMN protein results in degeneration of motor neurons, while extraneuronal manifestations have been regarded as a chance association with SMA. We report on heart defects in the subgroup of congenital SMA type I patients. Methods: Data were recruited from 65 unselected SMA I patients whose diagnosis had been confirmed genetically within the first 6 months of age. SMN2 copy numbers were analysed retrospectively and correlated with clinical findings including heart malformations. Results: Four (6%) patients had one copy of SMN2, 56 (86%) had two and five (8%) had three SMN2 copies. Three out of four (75%) patients with a single SMN2 copy had congenital SMA with haemodynamically relevant atrial or ventricular septal defects. Conclusions: Previous case reports of SMA I patients with congenital heart defects did not clarify whether the cardiac malformations were coincidental. Given the respective incidences of congenitally lethal SMA with a single SMN2 copy and of cardiac septal defects in humans, a chance association of both conditions would occur in less than one out of 50 million individuals. Our findings suggest that the SMN protein is relevant for normal cardiogenesis.